The CARMENES search for exoplanets around M dwarfs: first visual-channel radial-velocity measurements and orbital parameter updates of seven M-dwarf planetary systems - Trifonov, Trifon; Zechmeister, Mathias; Quirrenbach, Andreas; Reiners, Ansgar; Reffert, Sabine; Kaminski, Adrian; Seifert, Walter; Stürmer, Julian; Feiz, Carmen; Mandel, Holger; Rix, Hans-Walter; Sadegi, Sepideh; et al. (Arxiv, 2018)
Context: The main goal of the CARMENES survey is to find Earth-mass planets around nearby M-dwarf stars. Seven M-dwarfs included in the CARMENES sample had been observed before with HIRES and HARPS and either were reported to have one short period planetary companion (GJ15A, GJ176, GJ436, GJ536 and GJ1148) or are multiple planetary systems (GJ581 and GJ876). Aims: We aim to report new precise optical radial velocity measurements for these planet hosts and test the overall capabilities of CARMENES. Methods: We combined our CARMENES precise Doppler measurements with those available from HIRES and HARPS and derived new orbital parameters for the systems. Bona-fide single planet systems are fitted with a Keplerian model. The multiple planet systems were analyzed using a self-consistent dynamical model and their best fit orbits were tested for long-term stability. Results: We confirm or provide supportive arguments for planets around all the investigated stars except for GJ15A, for which we find that the post-discovery HIRES data and our CARMENES data do not show a signal at 11.4 days. Although we cannot confirm the super-Earth planet GJ15Ab, we show evidence for a possible long-period ($P_{\rm c}$ = 7025$_{-629}^{+972}$ d) Saturn-mass ($m_{\rm c} \sin i$ = 51.8$_{-5.8}^{+5.5}M_\oplus$) planet around GJ15A. In addition, based on our CARMENES and HIRES data we discover a second planet around GJ1148, for which we estimate a period $P_{\rm c}$ = 532.6$_{-2.5}^{+4.1}$ d, eccentricity
Version 1 vom 4. Oktober 2017, Version 3 vom 30. Januar 2018
Gesehen am 18.11.2022